Short-term resilience, long-term costs Reduced growth and increased erosion in the kelp Ecklonia radiata (phylum Ochrophyta) following repeated marine heatwaves - Wynn, Olivia J (Journal of phycology, 2025)
© 2025 The Author(s). Journal of Phycology published by Wiley Periodicals LLC on behalf of Phycological Society of America.